ANALISA GEOMETRI JALAN TERHADAP PRODUKTIVITAS ALAT ANGKUT DALAM KEGIATAN PENGANGKUTAN MATERIAL TIMBUNAN DI PTSUMATERA PEMBANGKIT MANDIRI KECAMATAN PAHAE JULU KABUPATEN TAPANULI UTARA PROVINSI SUMATERA UTARA - Nainggolan, Roy Pronsen; Marpaung, Nalom D; Debataraja, Semangat Marudut Tua (LPPM ISTP, 2023)
The research was conducted at PT. Sumatra Pembangkit Mandiri, which is engaged in hydropower. The road is one of the factors that greatly influence this research. Piled material hauling activities are influenced by the geometry of the road. The road geometry includes straight road width, bends, road grade and super elevation. Based on the actual calculation, the production is 124.56 LCM/hour. After doing theoretical calculations, the production is 209 LCM/hour. From the results of the analysis of the road geometry obtained with a distance of 500 m, the road segment is divided into 12 segments, which consist of 8 straight roads and 4 curved roads. The actual straight road width in the field starts from 5-6 meters while the minimum road width is 7 meters, in segments A-B to L-M it is necessary to widen the road. The actual width of the bend road starts from 6-7 meters, while the minimum road width of the bend is 8 meters, the C-D, E-F, H-I and J-K segments do not meet the minimum road conditions, so it is necessary to widen the bend road. The actual road grade ranges from 1.4-20.6%, while the maximum road grade is 8%, the E-F to L-M road grade segments must be repaired because they exceed the maximum road grade. The actual superelevation ranges from 1.4-1.05, while the minimum superelevation is 1.01 meters, the E-F and K-L segments require additional superelevation height because it is less than the maximum superelevation value.Based on field analysis using actual road geometry data, the cycle time obtained is 1415 seconds, and the theoretical cycle time is 841.5. Then the calculation of production per/hour using the cycle time value is obtained, the actual production obtained is 124.56 LCM/hour while the production using the theoretical obtained is 209.45 LCM/hour.